2014
DOI: 10.1163/15691497-12341319
|View full text |Cite
|
Sign up to set email alerts
|

Chinese National Oil Companies in Ghana: The Cases of cnooc and Sinopec

Abstract: This article uses the case of Ghana to provide insight into the policies and strategies used by, as well as the cooperation between, Chinese state actors in their quest for natural resources in Africa. In 2007, Ghana discovered commercial quantities of oil. While the so-called Jubilee oilfield was initially divided amongst primarily Western oil companies, in 2010 the China National Offshore Oil Corporation partnered with Ghana’s national oil company to try and purchase a stake in Jubilee. Although this bid was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In Ghana's context, Odoom (2015), Hardus (2014), and Phillips et al (2016) have focused on the engagement of transnational capital in the oil sector. Odoom (2015) examined Chinese engagement in Ghana's energy infrastructure and concluded that the deals favoured by the Chinese are appealing to both the Chinese and their African counterparts.…”
Section: Beyond the Resource Curse In Ghanamentioning
confidence: 99%
See 2 more Smart Citations
“…In Ghana's context, Odoom (2015), Hardus (2014), and Phillips et al (2016) have focused on the engagement of transnational capital in the oil sector. Odoom (2015) examined Chinese engagement in Ghana's energy infrastructure and concluded that the deals favoured by the Chinese are appealing to both the Chinese and their African counterparts.…”
Section: Beyond the Resource Curse In Ghanamentioning
confidence: 99%
“…The idea of 'quick and dirty' deals speaks to NPP interests such as the well-documented case of the E.O. Group (Hardus 2014, Phillips et al 2015. In 2004, the NPP government granted an oil block licence to the E.O.…”
Section: Inward Investment In Oil Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…62 In the case of the infrastructure loan, it is stipulated that 60 per cent of the contracts must go to Chinese companies, the main player being China's second-largest national oil company, Sinopec. 63 A word of caution on the volume and nature of these two loans is warranted, however. Both agreements were originally widely reported as being ODA-like and thus were included in datasets on Chinese official finance, including Aiddata.…”
Section: Ghanamentioning
confidence: 99%
“…Although quite a small body of work typically looking at communication strategies of Tullow Oil headquartered in the UK (Ampofo-Bekoe, 2014) and Chinese oil companies, their strategies, and how they are perceived in Ghana (Rupp, 2013;Hardus, 2014), this body of work has dispelled widespread myths. For instance, in looking at how Chinese oil companies such as China National Offshore Oil Corporation and SINOPEC have been working with the Ghanaian authorities and how such relationships have succeeded or failed in terms of how they have been received by the Ghanaian public but also in terms of long term energy strategy of the two countries, it shows that the oil companies are fairly independent of the Chinese state.…”
Section: Diverse Units Of Analysismentioning
confidence: 99%